Pattern of Prostate-specific antigen (PSA) in male participants 40 -70 years screened for prostate cancer during a medical outreach in a tertiary institution in Nigeria: A pilot study - Ima-Abasi, Bassey; Eyam, Eyam Sunday; Edoise M, Isiwele; Nchiewi, Ani Elemi; Ushie, Edem David; Ayi, Debua (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Objective: To study the pattern of prostate specific antigen (PSA) expression in apparently healthy male participants 40-70 years screened for prostate cancer during a medical outreach programme organized for the University of Calabar Community.Materials and method: Sixty one (61) apparently healthy men aged 40-70 years attending a medical outreach in the University of Calabar were recruited into the study. It was a cross sectional descriptive study in which screening for PSA was done using 1mL of blood sample collected via venipuncture from the participants while sitting and relaxed. Two drops of whole blood and a drop of buffer solution were introduced via a dropper onto a Diaspot rapid one-step test device and results read after five (5) minutes.Result: PSA values were categorized based on age groups of 40-49 years, 50-59 years, and 60- 70 years. 81.8%, 9.1% and 9.1% of the participants of age 40-49 years had values less than 4.0ng/ml, 4.0-10.0ng/ml, and above 10.0ng/ml respectively. 55.6%, 18.5%, and 25.9% of participants between 50-59 years age group had values of <4.0ng/ml, 4.0-10.0ng/ml, and  >10.0ng/ml respectively. While 66.7%, 16.7%, and16.7% of participants age 60 years and above had PSA values of <4.0ng/ml, 4.0ng/ml, and >10.0ng/ml respectively.Conclusion: This study showed the pattern of prostate-specific antigen (PSA) across the various age groups 40-70 years screened for prostate cancer. It revealed insidious prostatic disease even among apparently healthy males which further strengthened the fact that prostate cancer disease could be detected early through screening for prostate-specific antigen concentration. This is a wake-up call to health policy makers of the need to introduce routine screening programmes for aging males 40 years and above in Nigeria.